The Content Analysis of Fourth Grade student’s English Textbook of Cambodia - Samnangroth, Chea; Kina, Kam; Loch, Roeun (UNIB Press, 2025)
The current research examines English fourth-grade textbooks in Cambodia, with the goal of determining the alignment between the prescribed curriculum and the textbooks' actual content. It is hypothesized that differences between the two may affect students' language acquisition and academic performance in English. The study also seeks to identify potential areas for improvement in the design and delivery of English language education in Cambodian schools. The background of textbook content analysis research refers to the context and rationale for the study of textbook content analysis. This type of analysis examines the information, representations, and points of view included in educational textbooks. Moreover, by doing a content analysis of these educational resources, researchers can gain additional insight into the types of knowledge, values, biases, and points of view that students are being taught through textbooks. This analysis can help identify any imbalances or potential issues in the text, such as mistakes, stereotypes, or omissions. It can also provide recommendations for improving the standard and diversity of textbook content. However, the following conclusions are drawn from the evaluation's findings. First, the analysis demonstrates that the English textbook for fourth graders satisfies the standards of a fair textbook. It is decided that the English Fourth Grade textbook is reasonable because of the achievement rate of 78%. Second, the review reveals that Fourth Grade English has met the majority of the criteria needed for a textbook assessment. English Fourth Grade satisfied most of the requirements for curricular relevance, language appropriateness, presentation coverage, teaching and learning methodologies, accuracy of materials, andpresentation coverage of auxiliary learning resources.